2012
DOI: 10.1016/j.ultsonch.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of heat transfer by means of ultrasound: Application to a double-tube heat exchanger

Abstract: A new kind of ultrasonically-assisted heat exchanger has been designed, built and studied. It can be seen as a vibrating heat exchanger. A comprehensive description of the overall experimental set-up is provided, i.e. of the test rig and the acquisition system. Data acquisition and processing are explained step-by-step with a detailed example of graph obtained and how, from these experimental data, energy balance is calculated on the heat exchanger. It is demonstrated that ultrasound can be used efficiently as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…From the heating medium, delivered by the inlet (5), the jets are formed in the perforated partition (1). They are radially directed toward the inner surface of the cylindrical heat transfer wall (2), imping on it and then as the cooled streams are flowing towards the outlet (6). The heated medium is delivered through the inlet (7) and it is flowing in the space between the shell (4) and perforated partition (3).…”
Section: Minijets Heat Exchanger (Mjhe)mentioning
confidence: 99%
See 1 more Smart Citation
“…From the heating medium, delivered by the inlet (5), the jets are formed in the perforated partition (1). They are radially directed toward the inner surface of the cylindrical heat transfer wall (2), imping on it and then as the cooled streams are flowing towards the outlet (6). The heated medium is delivered through the inlet (7) and it is flowing in the space between the shell (4) and perforated partition (3).…”
Section: Minijets Heat Exchanger (Mjhe)mentioning
confidence: 99%
“…Another example of an active technique is the usage of ultrasound to vibrate the heat transfer surface or the fluid that flushes it. Gondrexon et al [5] and Legay et al [6] conducted studies to assess the effect of ultrasound on the heat exchanger efficiency, demonstrating that for the laminar flow the ultrasounds are particularly beneficial-the heat transfer coefficient can be more than doubled.…”
Section: Introductionmentioning
confidence: 99%
“…Klima et al [32] studied the effect of sonoreactor geometry on the distribution of ultrasonic intensity, the calculation together with experiment revealed that the whole reactor behaved like a resonator and the energy distribution depends strongly on its shape. Legay et al [33] designed a new kind of ultrasonically-assisted heat exchanger, it was demonstrated that ultrasound can be used efficiently as a heat transfer enhancement technique, even in such complex systems as heat exchangers.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Gondrexon et al [7]'s investigation showed that by ultrasound of 120 W/24 kHz overall heat transfer coefficient can increase up to 1.2 times of original value without treatment. Legay et al [8] gave experimental results that the heat transfer enhancement factor increased about 1.2-2.3 for double-tube heat exchanger by 35 kHz ultrasound. Guo [9] concluded experimentally that the ultrasonic frequency may have better effect than flow velocity and ultrasonic power for cooling water, and got the best descaling effects in case of ultrasound 30 kHz and 400 W, and 0.6 m/s flow velocity.…”
Section: Introductionmentioning
confidence: 99%